Nilai-Nilai Dalam Kabuki di Jepang - Sudarsih, Sri (KIRYOKU, 2017)
Kabuki is a part of culture the Japanese. Kabuki to progress changed and remain in existence in an age of modernization. Kabuki has meaning capable of inspired the Japanese people so must remain be preserved. Methods used by the author are description and interpretation. Material object  in this writing is Kabuki and formal object is axiology. Kabuki is a dramatic arts in which contains value of aesthetic, value of social,  value of heroism, and value of love.